Impact of environmental variables on fouling bryozoan species in the Eastern Aegean Sea. (April 2019) - Kocak, Ferah; Kucuksezgin, Filiz; Bakal, Ilkin
Abstract: Bryozoans are the major component of marine macro-fouling communities. In the study, the relations between bryozoan species and environmental variables were investigated at seven stations along the Aegean coast in August and December 2015. Constant bryozoan species in both sampling periods were Bugula neritina, Amathia verticillata, Shizoporella errata, Cryptosula pallasiana and Celleporaria brunnea . Their relationship with physico-chemical variables (Temperature, salinity, pH, dissolved oxygen, ammonium, nitrite and nitrate nitrogen, orthophosphate phosphorous, total phosphate, chlorophyll- a ) were analysed by means of logistic regression analysis. The result showed that temperature with B. neritina ; NH4 -N, oPO4 -P and TPO4 -P with A verticillata ; dissolved oxygen concentrations with S. errata and C. brunnea were positively related (p < 0.05). Highlights: Relation between bryozoan species and environmental variables was investigated. Distribution of bryozoan species was effected by temperature, salinity and pollutants. Temperature was significant predictor for B. neritina . The highest NH4 and PO4 concentrations were tolerated by A. verticillata .